THE EFFECT OF DRY NEEDLING THERAPY ON MYOFASCIAL PAIN SYNDROME - Pratiwi, Ni Made Dwita; Sutama, I Komang Reno; Widyadharma, I Putu Eka (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: One of the nonpharmacological management that can currently be used to treat Myofascial Pain Syndrome (MPS) is dry needling (DN). Dry needling is a pain intervention technique by inserting a solid needle into the skin to stimulate myofascial trigger points (TrPs). In a previous study conducted at Central Hospital in Bali, DN was shown to reduce pain and oral analgetic usage in patients with upper trapezius muscle MTrPs, but the effect of DN on overall life quality (such as sleep quality and depression) is still lacking. Objective: This research was conducted to find out whether there was an improvement in pain scale, depression and quality of sleep of health employees in Sanglah Hospital who experienced myofascial pain syndrome after dry needling therapy. Methods: an observational experimental design, which compares the difference of the Numerical Pain rating score, Pittsburg Sleep Quality Index, and Hamilton Depression Scale before and after DN. The study used a consecutive sampling method to reach the designated sample size. Results: A total of 53 samples followed the entire series of studies. The mean difference between NPRS before DN and after DN showed a significant result of p= 0.00 (<0.05), but in the aspect of PSQI and HDS no statistical difference. Conclusion: There is a trend of improvement in the quality of life after DN from pain scale, mood condition and sleep quality. However, this research still cannot show a link between DN therapy with depressive disorders and sleep quality.